Brands, costs and registration status of antimalarial drugs in the Kenyan retail sector - Amin, A; Snow, R (BioMed Central, 2005)
Background: Although an important source of treatment for fevers, little is known about the structure of the retail sector in Africa with regard to antimalarial drugs. This study aimed to assess the range, costs, sources and registration of antimalarial drugs in the Kenyan retail sector. Methods: In 2002, antimalarial drug registration and trade prices were established by triangulating national registration lists, government gazettes and trade price indices. Data on registration status and trade prices were compared with similar data generated through a retail audit undertaken among 880 randomly sampled retailers in four districts of Kenya. Results: Two hundred and eighteen antimalarial drugs were in circulation in Kenya in 2002. These included 65 "sulfur"-pyrimethamine (sulfadoxine-pyrimethamine and sulfalene-pyrimethamine (SP), the first-line recommended drug in 2002) and 33 amodiaquine (AQ, the second-line recommended drug) preparations. Only half of SP and AQ products were registered with the Pharmacy and Poisons Board. Of SP and AQ brands at district level, 40% and 44% were officially within legal registration requirements. 29% of retailers at district level stocked SP and 95% stocked AQ. The retail price of adult doses of SP and AQ were on average 0.38 and 0.76 US dollars, 100% and 347% higher than trade prices from manufacturers and importers. Artemether-lumefantrine, the newly announced first-line recommended antimalarial drug in 2004, was found in less than 1% of all retail outlets at a median cost of 7.6 US dollars. Conclusion: There is a need to ensure that all antimalarial drugs are registered with the Pharmacy and Poisons Board to facilitate a more stringent post-marketing surveillance system to ensure drugs are safe and of good quality post-registration.